Challenges in supplying skilled manpower at Enersea Resources Sdn Bhd / Hisham Ahmad - Hisham, Ahmad (2015)
Enersea Resources Sdn Bhd is one of many Oil & Gas companies in Malaysia that has been established since 1996. It is registered with many organizations and obtaining PETRONAS Licence, Ministry of Finance (MOF), Construction Industry Development Board (CIDB), Pusat Khidmat Kontraktor (PKK) and etc. One of many scopes of the business is Provision of Manpower Supply. ERSB helps support the industry by providing the needs of major oil & gas companies by solving their manpower shortages issue. This is because an anticipated business growth in the industry is contingent on the availability of skilled manpower in the country. Malaysia’s oil and gas sector is likely to require around 40,000 additional professionals in the next five years due to business growth and retirement or attrition in the sector. Core (technical) disciplines are more likely to account for the required manpower. The upstream sector is expected to see the maximum shortfall, due to high attrition and retirement. In the downstream sector, the refining and petrochemical sectors are witnessing substantial capacity additions that are translating into significant manpower requirements. The objective of this Project Paper is to determine whether the current number of skilled manpower is adequate or not to supply to the Oil & gas industry. The researcher wants to identify the factors for the influencing the provision of skilled manpower and wants to analyze the effects of inadequate skilled manpower to the company. A survey form was created from Google Form to find out the responses from personnel’s already working or looking for work in the Oil & Gas industry. The forms were emailed out to all respondents in early January 2015. For this Project Paper the respondents were asked on what they think is causing organizations’ inability to fill key roles. Nearly 27% of respondents associated it with the lacking of working experience. 25% of respondents actually blamed the inability to fill positions with will reduce competitiveness and productivity to the company. The survey results show that 24% of respondents think that the company should take steps to grow the talent pool and ensure access to the right skills that will help drive business results. Yet only 27% of respondents report that there is a shortage of manpower at the workplace.